THE FEATURES OF THE GEOLOGICAL STRUCTURE AND SEDIMENTATION OF THE EARLY CRETACEOUS SITE OF THE TERRESTRIAL VERTEBRATES OF SHESTAKOVO (KEMEROVO REGION, RUSSIA) - A. V. Podlesnov; B. I. Morkovin; E. N. Maschenko (Известия высших учебных заведений: Геология и разведка)
A new data on the geological structure, conditions of formation and faunal composition of the Early Cretaceous site of the terrestrial vertebrates by Shestakovo village (Kemerovo Region, Western Siberia) has been presented.The consolidated geological section has been constructed along the line Shestakovo-1 — Shestakovo-4 — Shestakovo-3 in which five lithologic members have been identified. A distribution of the vertebrates fauna taxons has been carried out along the selected lithologic members composing the Shestakovo series of the Ilek formation. A new data obtained during fieldwork in 2017 has made it possible to distinguish two main bony levels (lithologic members 3 and 5), which contain whole skeletons of reptiles. Lithofacies analysis has shown that the formation of the sites occurred under the conditions of the fluviolacustrine plain, where the channel, delta and floodplain facies were replaced by lake and lake-marshy facies, forming a series of sedimentation cycles. The latter are the evidence of the increase in the aridization of the climate upwards along the section. The given data calls into question previously expressed point of view about the coastal-marine or lagoon genesis of the Shestakovo series.